Structure and diversity of the vegetation of the Gorgona Island National Natural Park, Colombia - Vásquez-Vélez, Ana Isabel (Revista de Biología Tropical, 2014)
Gorgona is a continental island in the Pacific of Colombia. We studied the structure and diversity of its vegetation with 16 Gentry transects (total area 0.16ha) in nine sites on the island. With these data, we calculate Importance Value Index (IVI), distribution of individuals according to their height and diameter at breast height (DBH), cumulative species curves, and species diversity. The vegetation is mainly secondary forest, with remnants of primary forest on the hills. By density, frequency, and coverage, the most important family is Rubiaceae, with 0.275 IVF. The species with the highest IVI (0.157) isLacistema aggregatum (Lacistemataceae). In height and diameter classes (DBH), individuals have an inverted “J” distribution. The plant community has a Shannon-Wiener diversity index of 3.98. The cumulative species curve of the plant community does not level off even after more than ten transects. Transects were grouped in the similarity analysis but not strongly. There were species richness differences among transects. Rev. Biol. Trop. 62 (Suppl. 1): 13-26. Epub 2014 February 01.